Tsukiji : the fish market at the center of the world - Bestor, Theodore C. (California studies in food and culture, 2004)
Located only blocks from Tokyo's glittering Ginza, Tsukiji--the world's largest marketplace for seafood--is a prominent landmark, well known but little understood by most Tokyoites: a supplier for countless fishmongers and sushi chefs, and a popular and fascinating destination for foreign tourists.